Viabilitas Bacillus sp. Sebagai Agen Antagonis Patogen Tanaman Dalam Formulasi Berbahan Dasar Tepung - Dhirham Khusma Fakhruddin; Suhartiningsih Dwi Nurcahyanti (Fakultas Pertanian Universitas Jember, 2020)
Bacterial biopesticide formulations needed because the use of bacteria in the suspensions can reduce the ability to control disease in plants. Therefore, a bacterial suspension needs to be mobilized in the formula with a carrier (Carrier) to maintain the viability of bacteria. This research uses the formulation of Bacillus sp. made from rice flour, corn, tapioca and talc with the addition of urea, glucose and CMC. Formulation of Bacillus sp. flour based with the addition of urea, glucose and CMC were tested with Xanthomonas axonopodis pv. glycines and Colletotrichum sp. in vitro. The results showed that Bacillus sp. after formulation it is still able to maintain viabiitas and antagonistic power. Viability of Bacillus sp. the best is in the formulation of rice flour at 14 hsi at 4.94 X 1014 cfu / g while the inhibition zone of Bacillus sp. the best is the corn flour formulation of 13.1 mm and the inhibitory capacity of Bacillus sp. the best is in tapioca flour formulation at 42 hsi at 62.89%